Determinants of Revenue of Personal Income Tax at KPP Pratama Cibitung: A Perspective of Attribution Theory - Muslim, Ahmad Bukhori; Dian Sulistyorini Wulandari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research seeks to examine the impact of NPWP ownership obligations, tax audits, tax collection, and taxpayer awareness on the generation of tax revenues. The participants in this investigation were employees from the tax sector at KPP Pratama Cibitung, with a sample size of 100 tax employees selected through convenience sampling. Utilizing primary data collected through questionnaires, the study employed multiple linear regression tests conducted using SPSS Version 21 software to analyze and test hypotheses. The findings revealed that NPWP ownership obligations, tax audits, tax collection, and taxpayer awareness all demonstrated a noteworthy and positive influence on the receipts of personal income tax